SMT 113 - Social Media Emerging Tools - Linn Benton Virtual College (2018)
This course will assist students in developing effective and successful social media marketing campaigns. Students will have the opportunity to formulate a social media marketing plan with an appropriate target market using relevant social media channels and metric analysis and maintenance.